PERENCANAAN POROS MESIN PEMISAH KULIT DAN BIJI KACANG HIJAU - Andri, Muh.; Sudia, Budiman; Samhuddin, Samhuddin (Enthalpy : Jurnal Ilmiah Mahasiswa Teknik Mesin, 2018)
This research aims to determine the shaft planning that is safe and good, the moment of twisting or torque, the diameter of the shaft. In this study designed using Autodesk Inventor 2017. Software The material used toplan the shaft is carbon steel for the construction of the machine and rod steel which is cold machined for the shaft with the symbol S55C with a tensile strength of 66 kg/mm2.The results of shaft planning calculationsshow that the power plan is 7.165 kw, moment of torsion or torque with shaft rotation n1 (3600 rpm) of 1,938,530 kg. mm, and for shaft rotation n2 (960 rpm) of 7,269.4489 kg.mm, and the shear stress allowed is5.5 (kg/mm2), and the shaft diameter obtained a value of 28 mm, while the shear stress obtained a value of 1.688 kg/mm2. From the results above it can be seen that the value of shear stress that occurs is smaller than the shear stress value of the permit (???? < ????????) where ???????? = 5.5 kg/mm and the value of ???? = 1.688 kg/mm2, so that it can be concluded that the size The planned shaft is safe enough.Keywords: Shaft design, safe and good shaft, torque or torque moment, shaft diameter.